2004
DOI: 10.1677/joe.0.1810449
|View full text |Cite
|
Sign up to set email alerts
|

Human milk induces fetal small intestinal cell proliferation - involvement of a different tyrosine kinase signaling pathway from epidermal growth factor receptor

Abstract: Breast milk has non-nutritional protective effects on recipient infants. It has been speculated that bioactive substances present in human milk have important roles in protecting infants. However, the mechanisms by which such substances protect newborns are unclear. Therefore, we analyzed the growth-promoting activity of human milk and the intracellular signaling mechanism thereof using human fetal small intestinal (FHS 74 Int) cells. Epidermal growth factor (EGF) stimulated the proliferation of these cells. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Our data show that a range of growth factors and their receptors are expressed in infant rats as shown by their specific mRNA (both growth factors and receptors). This would explain why it is possible to induce a growth response either in vitro or in vivo with a variety of growth factors given in pharmacologic doses (1,2,(17)(18)(19)(20)(21)(22)(23). Our data did not show predominance of expression of any 1 conventional growth factor or their receptor in infant rats at an age when crypt fission is high.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Our data show that a range of growth factors and their receptors are expressed in infant rats as shown by their specific mRNA (both growth factors and receptors). This would explain why it is possible to induce a growth response either in vitro or in vivo with a variety of growth factors given in pharmacologic doses (1,2,(17)(18)(19)(20)(21)(22)(23). Our data did not show predominance of expression of any 1 conventional growth factor or their receptor in infant rats at an age when crypt fission is high.…”
Section: Discussionmentioning
confidence: 48%
“…A recent study by Mandir et al (16) investigated crypt fission by the same microdissection technique in rats at 3,4,6,9,12,18,26, and 48 weeks of age and found that crypt fission was 4.6% and 8.4%, respectively, at 3 and 6 weeks of age, before declining steadily to 1.5% at 48 weeks of life. In contrast to this study, our study investigated rats beginning at 7 days of life and therefore found an earlier broad peak of crypt fission of 10.5% at day 11 of life, but which had a broad tail until day 25 of life.…”
Section: Discussionmentioning
confidence: 99%
“…For studies of human milk-derived bioactives, the small intestinal FHs 74 Int. cell line has been widely used as a model (Ichiba et al, 1992;Kawamura et al, 1994;Wagner et al, 1998;Hirai et al, 2002;Takeda et al, 2004). We have shown that these small intestinal cells represent a very sensitive model for milk-derived bioactives (Purup et al, 2007).…”
Section: Cell-based Models Of the Gastrointestinal Tractmentioning
confidence: 99%
“…After fetal maturation, human milk becomes the foodstuff essential for the neonate's survival, and yet, it is more than its nutritional component for it has the capacity to stimulate cell growth and repair and provide immune protection and enhance immunocompetence [28, 29, [39][40][41][42][43][44][45]. Human milk contains numerous growth modulators [41,45,46] [66][67][68], and granulocyte colony-stimulating factor (CSF) [69], to name but a few.…”
Section: Transitioning From Amniotic Fluid To Human Milkmentioning
confidence: 99%
“…As summarized in Table 2, numerous bioactive substances in human milk, not found in formulas, are known to stimulate GI mucosal proliferation in adult and animal models and facilitate maturation and closure of the neonatal GI tract from the outside milieu [3, 39,40,66,72,115,116]. The physiological significance of milk-borne growth factors is widely accepted and supported by the following:…”
Section: Gut Permeabilitymentioning
confidence: 99%